Penjatuhan Pidana Kepada Pelaku Tindak Kekerasan Terhadap Istri Dalam Rumah Tangga Di Kota Soe (Studi Pada Putusan No. 39/Pid.Sus/2018/PN Soe). - Tagela, Yansen Umbu; Setiyono, Setiyono; Suratman, Teguh (MLJ Merdeka Law Journal, 2024)
Domestic violence (DV) is an issue that affects many societies,especially women, globally. This research aims to analyze theimposition of penalties against perpetrators of violence against wiveswithin households in Soe City, focusing on the case study of DecisionNo. 39/Pid.Sus/2018/PN Soe. This study employs a normative legalapproach through the analysis of legislation and a case study. Themain findings indicate that the imposition of penalties in thementioned decision does not fully reflect the expected justice.Firstly, the issue of non-comprehensive judicial considerations standsout. Judges tend to focus on individual defendant factors, such as thepresence of witnesses and criminal history, while aspects of social andpsychological impact on the victim receive inadequate attention.Secondly, the inadequacy of imposed sentences is evident. Despitebeing    grounded    in    relevant    legal    provisions,     the    one-yearimprisonment sentence for the defendant is deemed inappropriategiven the severity of the violence committed.The injustice in imposing penalties can convey the impression thatDV is trivialized by the judicial system, eroding the dignity ofvictims and undermining public trust in law enforcement. Theunaccounted social and psychological consequences in the verdict alsocarry significant implications for victims and society. To address this,it is recommended to provide training for judges on the social andpsychological impacts of DV, adopt a holistic approach in caseassessment, seek expert consultation, and consider a restorativejustice approach in enforcement. By taking these steps, it is hopedthat the judicial system can better reflect values of justice andprotection for DV victims.